Antioxidant and α-glucosidase inhibitory activities of the leaf and stem of selected traditional medicinal plants - Lee, Soo Yee; Mediani, Ahmed; A. H., Nur Ashikin; Abu Bakar Sajak, Azliana; Abas, Faridah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
The study was aimed to determine the antioxidant and α-glucosidase inhibition activities of the stem and leaf of five different traditional medicinal plants. The studied plants exhibited varied antioxidant and α-glucosidase inhibition activities. The antioxidant activities of the plants were determined through their free radical scavenging capabilities using DPPH assay. The most potent antioxidant activity was demonstrated by Neptunia oleracea with an IC50 of 35.45 and 29.72 μg/mL for leaf and stem, respectively. For α-glucosidase inhibition activity, Neptunia oleracea exhibited potential α-glucosidase inhibition activity with IC50 value of 19.09 and 19.74 μg/mL for leaf and stem, respectively. The highest total phenolic content (TPC) was also marked in Neptunia oleracea leaf and stem with value of 40.88 and 21.21 mg GAE/g dry weight, respectively. The results also showed that Strobilanthes crispus collected from two different locations possessed different levels of phenolic content, antioxidant and α-glucosidase inhibition activities. The study revealed that phenolic compounds could be the main contributors to the antioxidant and α-glucosidase inhibition activities with R values of 78.9 and 67.4%, respectively. In addition, antioxidant and α-glucosidase were positively correlated (R = 81.9%). Neptunia oleracea could be suggested as a potential natural source of antioxidant and antidiabetic compounds that can be used for the prevention or treatment of diabetes.